Molecular mechanism underlying aberrant expression of the connective tissue growth factor in paediatric pre-B cell acute lymphoblastic leukemia - Welch, Mathew D. (Curtin University, 2011)
Acute lymphoblastic leukaemia (ALL) is the most common cancer diagnosed in children aged 1-14 years. There have been vast improvements in clinical outcomes for children diagnosed with ALL with cure rates of up to 90% achievable for some forms of the disease. Despite these successes, some patients still relapse and the prognosis for these individuals is poor, thus there is still a great deal to be learned about the complex biology underlying ALL. Connective tissue growth factor (CTGF/CCN2) is a novel candidate gene in precursor B-cell (pre-B) ALL, and is aberrantly expressed in a high proportion (around 75%) of cases. While the CTGF protein has no known role in lymphocyte biology or haemopoiesis, CTGF gene expression has been associated with a poor outcome in children and adults, particularly in those patients deemed to have a high-risk of relapse. The primary aims of this study were to characterise CTGF expression in paediatric pre-B ALL tumours and cell lines, and to investigate what mechanisms were responsible for its deregulated expression by examining the contribution of both genetic and epigenetic factors.Analysis of a cohort of 73 primary paediatric pre-B ALL specimens, confirmed CTGF was aberrantly expressed in 75% of patients at heterogeneous levels. CTGF expression was found to be associated with prognosis in this cohort, as there was a trend toward lower 5 year relapse free survival (RFS) in patients with CTGFpos ALL (71% RFS in CTGFpos, 83% RFS in CTGFlow/neg), however this did not reach statistical significance (p=0.39). There was no difference in overall 5 year survival (OS) between patients with CTGFpos and CTGFlow/neg ALL. The association between CTGF expression and clinical features recorded at the time of biopsy was undertaken. These features included; age, gender, percentage blasts in bone marrow, peripheral haemoglobin level, spleen or lymph node involvement, or whether the sample was obtained at diagnosis or relapse. Patients with enlarged lymph nodes displayed a lower mean CTGF expression compared to those patients with no lymph node involvement. A similar pattern was observed with patients exhibiting enlargement of the spleen, however this did not reach statistical significance. No other clinical features were associated with CTGF expression.Analysis of global gene expression patterns in three independent paediatric pre-B ALL cohorts (PMH; n=73, Ross; n=118, Kang; n=207), identified five genes that were highly correlated with CTGF expression; SOCS2, MEF2C, ADD3, GSN and DPYSL2. In silico analysis of the 5’ flanking sequences of these genes, as well as CTGF identified predicted binding sites for the two Ikaros family proteins IKAROS and HELIOS, with at least one HELIOS site present in the 5’ flanking sequence of all correlated genes. This suggested a possible role for Ikaros family proteins in modulating CTGF gene expression. Subsequent analysis of a microarray cohort recently characterised for IKAROS gene deletions revealed that mutations or deletions within the IKAROS coding region were significantly associated with higher mean CTGF gene expression, implying that a loss of IKAROS function may promote activation of the CTGF locus. This is the first evidence implicating the Ikaros family of lymphoid transcriptional regulators in deregulation of the CTGF locus.Northern blotting of RNA from B-lineage ALL cell lines uncovered evidence of alternative splicing of CTGF mRNA. Non-canonical transcripts of approximately 1.3kb and 1.6 kb were hybridised by a CTGF-specific probe in extracts from all CTGFpos cell lines. Sequencing of cDNA fragments as well as 5’ and 3’ RACE products from a cell line with the highest level of CTGF expression revealed a number of CTGF transcripts exhibiting internal deletions of exons 2 and 3, as well as truncation of exons 1 and 4. 3’ RACE also identified a 1.3kb transcript that was devoid of 3’ UTR regulatory elements as a result of premature polyadenylation. These findings represent the first direct evidence of alternative splicing of CTGF pre-mRNA in any tissue type and further investigation is warranted to fully characterise these tumour-associated transcripts and their protein coding potential.Structural changes within the genome are common in leukaemia and deletions affecting the long arm of chromosome 6 occur in around 30% of cases of pre-B ALL. To investigate whether deregulation of CTGF expression has a genetic basis, the CTGF locus at 6q23.1 was investigated for structural alterations or mutations. Southern blotting performed in seven B-lineage ALL cell lines (4 CTGFpos, 3 CTGFneg) confirmed that the CTGF locus was not cytogenetically rearranged. Furthermore, analysis of CTGF copy number by qPCR in primary paediatric pre-B ALL specimens (n=17) and B-lineage ALL cell lines (n=7) confirmed that gene amplification could not account for CTGF overexpression. Sequencing of the CTGF promoter and 3’ UTR in three B-lineage ALL cell lines confirmed that there were no mutations affecting these important regulatory regions, although one cell line harboured the rs6918698 -739 C>G SNP, which is predicted to disrupt SP3-mediated repression of CTGF gene expression.Epigenetic regulation of gene expression is frequently altered in neoplasia. The CTGF locus contains a CpG island, and methylation of this region was found to be inversely correlated with CTGF gene expression in B-lineage ALL cell lines, as assessed by both methylation-specific PCR and by bisulfite sequencing. Bisulfite sequencing of primary tumour specimens revealed that hypomethylation of the CTGF locus was a widespread feature of pre-B ALL. By contrast, analysis of primary T-ALL specimens demonstrated extensive methylation at the CTGF locus, indicating that CTGF may be permissive for expression specifically in pre-B ALL.This study has highlighted several novel aspects of CTGF expression in pre-B ALL, including a potential role for Ikaros family proteins in regulating the CTGF locus, and the existence of CTGF mRNA transcripts generated through alternative pre-mRNA splicing. Investigation of mechanisms promoting CTGF gene expression in pre-B ALL revealed that the rs6918698 C>G SNP was present in one pre-B ALL cell line. Hypomethylation of the CTGF locus was a notable feature of primary pre-B ALL specimens and was in contrast to the hypermethylation observed in 2 T-ALL specimens and CD34pos bone marrow cells. These findings will direct future research to elucidate the complex mechanisms regulating CTGF expression in pre-B ALL. It is anticipated that illuminating the role of CTGF in the pathogenesis of ALL may result in significantly improved patient outcomes through the development of targeted and less toxic therapies, and through improved risk-based stratification of patients to ensure those at a high risk of relapse are directed toward an appropriate level of therapeutic intervention.